Preparation of supported lipid membranes for aquaporin Z incorporation - Li, Xuesong (2013)
There has been a recent surge of interest to mimic the performance of natural cellular membranes by incorporating water channel proteins-aquaporins (AQPs) into various ultrathin films for water filtration applications. To make biomimetic membranes one of the most crucial steps is preparing a defect-free platform for AQPs incorporation on a suitable substrate. In this study two methods were used to prepare supported lipid membranes on NF membrane surfaces under a benign pH condition of 7.8. One method was direct vesicle fusion on a hydrophilic membrane NF-270; the other was vesicle fusion facilitated by hydraulic pressure on a modified hydrophilic NF-270 membrane whose surface has been spin-coated with positively charged lipids. Experiments revealed that the supported lipid membrane without AQPs prepared by the spin coating plus vesicle fusion had a much lower defect density than that prepared by vesicle fusion alone. It appears that the surface roughness and charge are the main factors determining the quality of the supported lipid membrane. Aquaporin Z (AqpZ) proteins were successfully incorporated into 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) liposomes and its permeability was measured by the stopped-flow experimental procedure. However, after the proteoliposomes have been fused onto the modified substrate, the AqpZ function in the resultant membrane was not observed and AFM images showed distinct aggregations of unfused proteoliposomes or AqpZ proteins on the substrate surface. It is speculated that the inhibition of AqpZ function may be caused by the low lipid mobility on the NF membrane surface. Further investigations to evaluate and optimize the structure-performance relationship are required.